Interpretation of Youth from the Thinking of Badiuzzaman Said Nursi - Alizaman D. Gamon; Maulana Akbar Shah @ U Tun Aung; Mohammed Farid Ali; Mariam Saidona Tagoranao (International Islamic University Malaysia, 2024)
Indexed by MyCite